2019
DOI: 10.1007/978-3-030-25572-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Leibniz on the Continuity of Space

Abstract: The present essay describes Leibniz's foundational studies on continuity in geometry. In particular, the paper addresses the long-debated problem of grounding a theory of intersections in elementary geometry. In the early modern age, in fact, several mathematicians had claimed that Euclid's Elements needed to be complemented with additional axioms in order to ground the existence of the intersection points between straight lines and circles. Leibniz was sensible to similar foundational issues in the Euclidean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…no point), even though there are more divisions of bodily parts than can possibly be expressed by any finite number. (De Risi [34], 2019; emphasis in the original). This use of the term "syncategorematic infinity" refers to matter or space, closely related to indefinite divisibility.…”
Section: Extensions and Predicatesmentioning
confidence: 99%
See 1 more Smart Citation
“…no point), even though there are more divisions of bodily parts than can possibly be expressed by any finite number. (De Risi [34], 2019; emphasis in the original). This use of the term "syncategorematic infinity" refers to matter or space, closely related to indefinite divisibility.…”
Section: Extensions and Predicatesmentioning
confidence: 99%
“…If any opponent tries to contradict this proposition, it follows from our calculus that the error will be less than any possible assignable error since it is in our power to make this incomparably small magnitude small enough for this purpose inasmuch as we can always take a magnitude as small as we wish. ( Meanwhile I have shown that these expressions are of great use for the abbreviation of thought and thus for discovery as they cannot lead to error, since it is sufficient to substitute for the infinitely small, as small a thing as one may wish, so that the error may be less 34 Note that Ishiguro's sentence "If magnitudes are incomparable, they can be neither bigger nor smaller" [50, p. 88] involves an equivocation on the term incomparable: if incomparable is taken to mean the definition from the theory of partially ordered sets, then this is a tautology (roughly "if magnitudes cannot be compared, then they cannot be compared"); if incomparable is taken to mean "any positiveinteger multiple is still less than any positive real" then Ishiguro's statement is mathematically incorrect, for the hyperreals are a totally ordered field, hence every element can be compared with any other. than any given amount, hence it follows that there can be no error.…”
Section: Leibniz Goes On To Discuss a Few Examples And Concludesmentioning
confidence: 99%
“…Other sources make clear that the Greeks regarded lines (curved or straight) as the traces of a motion. 9 In particular, most modern mathematicians, steeped in set theory from their youth, think that a line is equal to the set of its points. This was definitely not the Greek conception.…”
Section: Linesmentioning
confidence: 99%
“…However, the default in Euclid, though not necessarily in all Greek geometry, is that lines are straight. We follow Euclid.8 A referee pointed out[29], which gives an axiomatic framework for a part of geometry in which the collapsible compass is preserved 9. This view of lines goes back at least to Aristotle; see[28, p. 79], where Proclus says Aristotle regarded a line as "the flowing of a point.…”
mentioning
confidence: 99%
See 1 more Smart Citation